Coumarin-based Strategies for Breast Cancer: A Multifaceted Perspective - Sharma, Yash; Kalra, Sourav; Vashisht, Ankit; Sharma, Rajiv (Mini Reviews in Medicinal Chemistry, 2025)
Breast cancer remains the most prevalent cancer among women worldwide, with increasing toxicity and resistance to current therapies posing a serious challenge to healthcare systems. The urgent demand for more effective and safer treatments has highlighted coumarin, a naturally occurring compound with a unique ring structure, due to its promising potential in combating breast cancer. Over the past three decades, numerous synthetic coumarin derivatives have been developed to enhance therapeutic efficacy. This review provides a comprehensive analysis of 18 reported coumarin-based compounds, focusing on their design strategies, mechanisms of action, and structure-activity relationships (SAR). Molecular docking studies targeting key enzymes, including tyrosine kinases, topoisomerases, and serine/threonine kinases, were examined to evaluate binding affinities and interaction patterns. Substitutions at the 3- and 6-positions of the coumarin scaffold were found to impact target binding significantly. Critical interactions, including hydrogen bonding, van der Waals forces, and hydrophobic contacts, were correlated with experimental anticancer activities, offering valuable insights into ligand-protein complex stabilization. Overall, the analysis underscores the potential of coumarin derivatives as promising leads for the rational design of novel anticancer agents with improved efficacy and selectivity.
Keywords: molecular docking and ligand-receptor interaction